2020
DOI: 10.1063/5.0002835
|View full text |Cite
|
Sign up to set email alerts
|

Compositional dependence of crystallization temperatures and phase evolution in hafnia-zirconia (HfxZr1−x)O2 thin films

Abstract: Polymorphic (HfxZr1−x)O2 (HZO) thin films exhibit ferroelectric, dielectric, and antiferroelectric properties across a wide compositional range due to the existence of orthorhombic, monoclinic, and tetragonal phases. To better understand the phase stability across the HfO2–ZrO2 compositional range, we investigate the structural evolution of HZO thin films in situ via high-temperature x-ray diffraction (HTXRD) for five different compositions [ZrO2, (Hf0.23Zr0.77)O2, (Hf0.43Zr0.57)O2, (Hf0.67Zr0.33)O2, and HfO2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…[ 28 ] Hafnium zirconium oxide (Hf 1– x Zr x O 2 , HZO) alloys, in particular, have generated wide interest due to the observation of robust hysteresis behavior with a lower thermal budget compared to most other HfO 2 ‐based ferroelectrics. [ 29,30 ] Zirconium oxide also demonstrates the largest dopant concentration window in which ferroelectric polarization response is observed (≈10–80 at%). [ 9 ] For other dopants, a ferroelectric response is generally observed for concentrations between 1 and 10 at%, excluding lanthanum, [ 31 ] which has been shown to stabilize orthorhombic HfO 2 with doping concentrations up to 20 at%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] Hafnium zirconium oxide (Hf 1– x Zr x O 2 , HZO) alloys, in particular, have generated wide interest due to the observation of robust hysteresis behavior with a lower thermal budget compared to most other HfO 2 ‐based ferroelectrics. [ 29,30 ] Zirconium oxide also demonstrates the largest dopant concentration window in which ferroelectric polarization response is observed (≈10–80 at%). [ 9 ] For other dopants, a ferroelectric response is generally observed for concentrations between 1 and 10 at%, excluding lanthanum, [ 31 ] which has been shown to stabilize orthorhombic HfO 2 with doping concentrations up to 20 at%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–14 ] Among metal oxides used as an insulator, zirconia thin films can offer a better option in a wide variety of applications owing to their solution processability, acceptable relative permittivity (ε r ), low leakage current density ( J leak ), and high transparency in the visible region. [ 15–17 ] It should be noted that the features of the wide bandgap formation and high bandgap tunability through stoichiometric and morphological manipulations render group IV transition metal oxides such as zirconia, hafnia, and titania considered notably interesting. Therefore, exploring the behavior of electrons, the energy distribution of states, the effects of defects, and relations thereof in zirconia thin films is expected to provide a useful knowledge base for metal‐oxide‐based future electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxides have been the subject of intense study due to their use in many technologies such as nanoelectronics, sensors, photocatalysis, etc., both in amorphous and crystalline forms. HfO2 can be found in a variety of phases such as cubic, tetragonal, monoclinic, and more recently the orthorhombic [1][2][3][4] . For thin films which are the subject of this proposal, crystallization usually proceeds by nucleation in the tetragonal phase due to the surface energy effect but the monoclinic phase takes over and appears the most dominant 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…One should keep in mind that film thickness is an important parameter. HfO2 films with thickness around 100 nm are known to crystallize partially at 250°C and in general, the crystallization onset temperature is inversely proportional to the film thickness 4,5,10,13,30,[44][45][46][47] . For example, Kukli et al demonstrated thicknessdependent crystallization for HfO2 films deposited from tetrakis ethylmethylamino hafnium (TEMAHf) and H2O at 250°C: 5 nm film are amorphous, 30 nm barely crystalline, and for 45nm films the presence of crystallization is evident 48 In this manuscript, we will demonstrate that HfO2 films with thicknesses from 6 to 34 nm deposited at 250-275°C on GaAs oxide surfaces are polycrystalline and contain a variety of crystalline phases.…”
Section: Introductionmentioning
confidence: 99%